Fear psychosis : Marketing strategy for next gen buyers (Vallis Aurea, 2023)
Marketing has entered the holistic era, where businesses act as unified entities, targeting all potential segments for sustainable growth. Millennials, the largest group of buyers and influencers globally, now dominate the workforce and represent a powerful economic force. They are rational, less emotional, highly evaluative, and have strong buying power and access to vast information. Due to their logical decision-making and lack of emotional attachment to brands, keeping them loyal and engaged is a major challenge for marketers.To influence Millennials, companies have adopted strategic methods to tap into their deeper concerns—especially fear. This generation responds most to threats concerning health, safety, and security. By creating awareness of these risks and offering solutions, businesses position themselves as genuinely caring. This approach, known as Fear Psychosis in marketing, extends emotional tactics by leveraging fear to prompt action. It has proven effective in engaging Millennials, influencing their decisions, and building trust. Fear-based marketing triggers psychological responses that make customers feel protected by the brand, fostering continued loyalty and repeat purchases.